New horizons in eastern humanism Buddhism, Confucianism and the quest for global peace - Tu, Weiming 1940-; Ikeda, Daisaku 1928- (I. B. Tauris, 2011)
China now attracts global attention and headlines that are directly proportionate to its increasing economic and geopolitical power. But for several millennia the philosophy that has guided and shaped the soul of China is not modern Communism, or even new forms of capitalism, but rather Confucianism. And one of the most striking phenomena relating to China's ascendancy on the world stage is a burgeoning interest, throughout Asia and beyond, in the humanistic culture and value-system that underlie Chinese politics and finance: particularly the complex, multi-layered and sophisticated thought of Confucius as passed on in the Analects.